TAPN: Test Automation’s Pyramid of Needs - Rodrigues, Anderson; Dias-Neto, Arilo C.; Bezerra, Allan (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2015)
Testing is an essential activity to ensure quality of software systems, but it is expensive and time consuming. Thus, testing automation would be an alternative to improve test productivity and save costs. However, many organizations refuse to use test automation or had failed on implement it because they do not know how to deal with the implementation of a test automation strategy fitted to their goals and expectations. Most of them underestimate or have no knowledge about test automation factor of success. In addition, although there are many works and maturity models focused on improving the testing process, few ones focus on test automation issues. The main contribution of this paper is to propose a hierarchical model called Test Automation’s Pyramid of Needs (TAPN). TAPN is inspired in the Maslow’s Pyramid of Needs administration theory and it comprises five levels that influence on the success of test automation initiatives in software organizations. TAPN intends to help organizations to build their test automation strategy using good practices in test automation captured from the technical literature.